FAKTOR RISIKO KEJADIAN HIPERTENSI PADA USIA DEWASA MUDA (20-44) DI WILAYAH KERJA PUSKESMAS KANDAI TAHUN 2022 - Fitrah Amalia; Asnia Zainuddin; Irma Irma (FKM Universitas Halu Oleo, 2022)
Hypertension is a body condition where there is an increase in systolic blood pressure 140 mmHg or systolic blood pressure ≥ 90 mmHg. This study aims to determine the risk factors for family history, physical activity, obesity and smoking habits at the Kandai Health Center in 2022. This study used design case control. The population in this study were all patients who came for treatment at the Kandai Health Center in 2022. The sample in this study was 120 consisting of 60 cases and 60 controls, sampling using simple random sampling technique. The results showed that family history obtained an OR = 99 (CI; 28,512-334,751), physical activity obtained a value of OR = 0.655 (CL; 0.246-9.478), obesity obtained an OR = 2.466 (CI; 0.193-0.853), and habits smoking obtained OR value = 1.238 (CL; 0.590-2.596). From the 120 research samples used, it can be concluded that the variables of family history, obesity, and smoking habits are risk factors for the incidence of hypertension in the work area of the Kandai Public Health Center in 2022, while the physical activity variable is not a risk factor for the incidence of hypertension